1998
DOI: 10.1259/bjr.71.845.9691895
|View full text |Cite
|
Sign up to set email alerts
|

Improved diagnostic accuracy in dynamic contrast enhanced MRI of the breast by combined quantitative and qualitative analysis.

Abstract: To develop an optimized interpretation strategy of dynamic contrast enhanced breast MRI based on a combination of quantitative and qualitative criteria, the features of 120 histopathologically verified lesions were retrospectively analysed on contrast enhanced dynamically acquired (before and 1, 2, 4 and 7 min following injection of 0.2 mmol kg-1 gadolinium-DOTA) three-dimensional gradient echo images. Quantitative criteria, based on relative signal intensity measurements and qualitative morphological features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 30 publications
4
56
0
6
Order By: Relevance
“…Contrast-enhanced magnetic resonance imaging (MRI) has been shown to have a high sensitivity (86% to 100%) for detecting breast cancer in high-risk asymptomatic and symptomatic women, although reports of specificity have been more variable (37% to 97%). [23][24][25][26][27] The American Cancer Society now recommends MRI screening in addition to mammograms for women who meet at least one of the following conditions 28 :…”
Section: Screening Strategies In High-risk Womenmentioning
confidence: 99%
“…Contrast-enhanced magnetic resonance imaging (MRI) has been shown to have a high sensitivity (86% to 100%) for detecting breast cancer in high-risk asymptomatic and symptomatic women, although reports of specificity have been more variable (37% to 97%). [23][24][25][26][27] The American Cancer Society now recommends MRI screening in addition to mammograms for women who meet at least one of the following conditions 28 :…”
Section: Screening Strategies In High-risk Womenmentioning
confidence: 99%
“…THE QUALITY OF MAGNETIC RESONANCE (MR) images of breast has been enhanced by a number of technical improvements, including improved fat saturation (1,2), Dixon-based methods (3)(4)(5)(6)(7)(8)(9)(10)(11) for improved fat and water separation, and dynamic contrast-enhanced MR imaging (MRI) (12)(13)(14)(15)(16)(17). Despite these advances, the high sensitivity of MRI combined with limited specificity still leads to a large number of false positives (18 -25).…”
mentioning
confidence: 99%
“…For the detection of invasive carcinomas, previous studies reported sensitivities from 90% to almost 100% whereas specificity was between 75% and 85% [26][27][28]. In DCIS, detection rates of 70-80% were described [29][30][31].…”
Section: Discussionmentioning
confidence: 99%